Analisis Penerapan Perencanaan Agregat dan S&OP dalam Mendukung Produksi UMKM Dapoer Feraaa - Antika Dwi Pramita Sari; Nabila Rachmah; Sinta Nurrohmah; Haris Hendra Setiawan; Abd Kevin Arigi (Jurnal Ekonomi dan Bisnis Digital, 2026)
Production planning is an important aspect of SME operations because it influences the ability of a business to meet consumer demand effectively and efficiently. This study aims to analyze the implementation of Aggregate Planning and Sales and Operations Planning (S&OP) at Dapoer Feraaa SME in Lamongan Regency. The research employed a descriptive qualitative method with a case study approach. Data were collected through interviews, observations, and documentation related to production and sales activities. The results indicate that Dapoer Feraaa has implemented production planning by considering sales levels, market trends, and consumer demand. The planning pattern tends to follow a chase strategy, in which production volume is adjusted according to changes in demand to minimize the risk of excess inventory. The implementation of Sales and Operations Planning (S&OP) is carried out through coordination between marketing and production activities to determine production quantities based on sales data, market conditions, and product evaluations. In addition, social media is utilized as a source of information to understand consumer responses and market trends that support production decision-making. Although the business still faces challenges such as demand fluctuations, limitations in the availability of certain raw materials, and pricing decisions, the implementation of Aggregate Planning and S&OP helps align production capacity with market needs. This study demonstrates that the application of these two concepts can support the effectiveness of production planning in SMEs.